IJCM_182A: Behavioural risk factors among under graduate medical students in North Kerala - Smitha M; Jayakrishnan T; Sruthikrishna P; Lakshmanan Anjali; Mohandas Bindu (Wolters Kluwer Medknow Publications, 2024)
Background: The World Health Organisation highlights that 60% of the morbidity and mortality from non communicable diseases are linked to lifestyle behavioural patterns .Primary risk factors include high fat and low fibre diet, lack of exercise, prolonged screen time, insufficient sleep, and the adoption of new habit and addictions. Since medical students are particularly prone to these risk factors, it is crucial to evaluate their lifestyle behaviours, recognising their role as future healthcare providers Objectives: 1. To assess anthropometric risk factors among the study population. 2. To assess the behavioural risk factors among the study population. Methodology: A cross sectional study was undertaken involving 150 undergraduate medical students in a private medical student in a private medical college. Data was collected through self administered questionnaire containing demographic details of the students, life style factors like diet, physical activity, screen time, habits and addictions. Data collected was entered into excel and analysed using SPSS 25. Results: Mean age of the study population was 22.3 (±1.5) years. Majority of the study participants were females (72.2%). Out of150 participants, 94.4% adhere to a non-vegetarian diet in which 15% reported daily consumption of soft drinks and 29% consume junk food daily. The participants who were overweight was found to be 33.4% in which 38.8% of the subjects are physically inactive and 22.2% reported inadequate sleep. Around 60 % of the participants use mobile phone most of the time. Conclusion: Behavioural risk factors such as unhealthy diet, inadequate sleep pattern, physical inactivity were prevalent among the undergraduate medical students.